PENGARUH BIMBINGAN KELOMPOK DENGAN TEKNIK SOSIODRAMA TERHADAP KOMUNIKASI INTERPERSONAL - Nindi Arsita, Jesika; Fitriana, Siti; Widiharto, Chr.Argo (Prodi Bimbingan dan Konseling universitas PGRI Semarang, 2023)
The aim of the study was to determine whether or not there was an influence of group guidance using the sociodrama technique on interpersonal communication at SMP N 37 Semarang. This type of research is quantitative. The research method used in this study was a pre-experimental design with a one- group pretest-posttest research design. The population of this study was class VIII E SMP N 37 Semarang. Samples taken by 10 students with purposive sampling technique. The data in this study were obtained through a psychological scale. The Paired Sample T test shows a significant number of pre- test and post-test values with a significant value (2-tailed) p = 0.000 <0.05 thus Ho is rejected and Ha is accepted, which means